Exploring language of communication in interpersonal relationships (2017)
The language of communication is the glue that holds people in a relationship. It is an essential component in developing a long lasting relationship, because both partners make choices about their language of communication to negotiate the nature of their relationship. Interpersonal relationship develops through language of communication when two people meet for the first time. However, the use of language between them will either move the relationship forward or lead to the termination of the relationship. The paper seeks to address the extent to which language of communication can be applied to building and maintaining interpersonal relationship among partners. The paper explores the speech act theory to understand the meaning in the use of words. The concept of language in this paper was used as a form of communication among partners in relationships which leads to relationship maintenance or deterioration. While mentioning some challenges of language of communication the paper suggest some strategies for improving them in interpersonal relationships. The paper conclude on the role that language as a communication vehicle can play in improving various relationships in order to avoid conflict situations that always arise from interpersonal relationships.